PENYULUHAN KESEHATAN REPRODUKSI TERHADAP REMAJA TINGKAT SMP - SMA DI PONDOK PESANTREN IBNU ABBAS KOTA SERANG, BANTEN - Gema Ikrar Muhammad; Husnul Amalia; Nur’aini; Sely Novita (Tensile : Jurnal Pengabdian Kepada Masyarakat, 2024)
Adolescents are potential human resource assets as the future successor of the nation. Adolescents are vulnerable to various problems related to sexual and reproductive health, including sexual violence, reproductive hygiene related to the risk of sexually transmitted infections, the risk of unwanted pregnancy. Responding to these conditions, the Biology Study Program, Faculty of Mathematics and Natural Sciences, Pamulang University conducted Community Service (PKM) which touched directly on the target object (adolescents) by introducing reproductive organs and reproductive health to students at Pondok Pesantren Tahfidz Quran Ibnu Abbas (Ponpes Ibnu Abbas), Taktakan District, Serang City, Banten Province. The PKM was carried out within the time span of October 2023 - January 2024, with the training conducted in November 2023. PKM activities use socialization and counseling methods on reproductive organs and reproductive health, in collaboration with the Midwifery Study Program of Bhakti Kencana University Serang. PKM activities of Biology Study Program Lecturers, Faculty of Mathematics and Natural Sciences, Pamulang University, were very well received by the community (Ponpes Ibnu Abbas), and were considered important to be carried out to educate and provide real benefits to the community, especially in the city of Serang. Keywords: Community services, Reproductive health, Ponpes Ibnu Abbas